Bioorganic Mineral Fertilizer on the Basis of Black Manage, Phosphorite Raw Materials and Biopreparts of Microorganisms - Kanoatov Khayrullo; Namazov Shafoat; Temirov Uktam; Usanboyev Najimuddin; Pirimov Tuychi (E3S Web of Conferences, 2024)
This article presents the results of studies on the production of bioorganic mineral fertilizers by treating a mixture based on black manure and phosphorite raw materials with a solution that accelerates the humification of organic matter, binds molecular nitrogen and enriches it with physiologically active substances, as well as microorganisms that play an important role in soil fertility. Based on the results of the study, it was found that treatment of a mixture based on black manure and phosphorite raw materials with a solution containing beneficial microorganisms accelerates the humification of organic matter, increases the conversion of phosphorus and reduces the release of nitrogen and organic matter into the gas phase.